Systematic assessment of the brown tree frog (Anura: Pelodryadidae: Litoria ewingii) reveals two endemic species in South Australia - Parkin, Tom; Rowley, Jodi J. L.; Elliott-Tate, Jessica; Mahony, Michael J.; Sumner, Joanna; Melville, Jane; Donnellan, Stephen C. (Zootaxa, 2024)
The brown tree frog (Litoria ewingii) is a relatively widespread, commonly encountered pelodryadid frog from south-eastern Australia, known for its characteristic whistling call. The distribution of Litoria ewingii spans over more than 350,000 km2, encompassing a range of moist temperate habitats, and is fragmented by well-known biogeographic barriers. A preliminary analysis of mitochondrial DNA sequences revealed evidence for deep phylogenetic structure between some of these fragmented populations. In this study, we sought to re-evaluate the systematics and taxonomy of Litoria ewingii sensu lato by analysing variation in nuclear and mitochondrial DNA, adult morphology and male advertisement calls throughout the species’ range. Our analyses reveal two additional, deeply divergent and allopatric lineages in South Australia. We herein re-describe Litoria ewingii from Tasmania, southern New South Wales, Victoria and south-eastern South Australia, resurrect the name Litoria calliscelis for a species occurring in the Mount Lofty Ranges and Fleurieu Peninsula in South Australia, and describe a new species, Litoria sibilus sp. nov., endemic to Kangaroo Island.